Asset Structure , Profitability And Business Risk on Capital Structure - Salsa Rizky Dwi Annisa; Hardiyanto Wibowo; Novi Dirgantari; Dwi Winarni (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of asset structure, profitability, and business risk on the capital structure of food and beverage sub-sector manufacturing companies from 2019 to 2021. The sample selection method uses a purposive sampling technique for food and beverage companies listed on the Indonesia Stock Exchange. (IDX) 2019-2021. The sample for this study was 33 with a total of 11 food and beverage companies observed during 2019–2021. This type of research data uses a quantitative approach and secondary data sources taken from www.idx.com with descriptive data analysis techniques, classical assumptions, multiple linear regression analysis, coefficient of determination (R2), T test and F test using SPSS 25. The results of this study This shows that the asset structure variable has an effect on the capital structure, while the profitability and business risk variables have no effect on the capital structure.